2020
DOI: 10.3390/biology9080224
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bone Definition and Finite Element Parameters in Bone and Dental Implants Stress: A Literature Review

Abstract: Bone plays an important role in dental implant treatment success. The goal of this literature review is to analyze the influence of bone definition and finite element parameters on stress in dental implants and bone in numerical studies. A search was conducted of Pubmed, Science Direct and LILACS, and two independent reviewers performed the data extraction. The quality of the selected studies was assessed using the Cochrane Handbook tool for clinical trials. Seventeen studies were included. Titanium was the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(66 citation statements)
references
References 43 publications
2
64
0
Order By: Relevance
“…To this end, abutments of three different heights were created, with an identical size to the entire prosthetic system. The use of FEA for biomechanical studies in oral implantology is widely accepted in the scientific literature, as shown by numerous meta-analyses and systematic reviews [34,35], and allows us to perform studies that would be more complex in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, abutments of three different heights were created, with an identical size to the entire prosthetic system. The use of FEA for biomechanical studies in oral implantology is widely accepted in the scientific literature, as shown by numerous meta-analyses and systematic reviews [34,35], and allows us to perform studies that would be more complex in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 15 ] Following this, a full mouth simultaneous posterior biting load of 150 N was given to simulate the normal masticatory force. [ 16 26 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…The less stress distribution in All on Four concept was due to increased number of implants, tilted posterior implants and increased bone to implant contact which inturn increased the surface area and reduced the cantilever length due to the increased AP implant spread. [ 10 16 26 27 28 29 30 31 ] On the another hand, the occlusion given also greatly influences the biomechanical success of both All-on-Four and Trefoil concept. Implant-protected occlusion has to be given for the long-term success of the implant-supported full mouth rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Finite elements analysis was acted as a brilliant method in the medical field overall, and in field of dentistry in specific. The results providing through software models based on the "finite elements considerations, as mesh definitions and elements, material properties, and margin and applying loads settings" [19]. Many stress analysis dental cases have been achieved by finite element technique at static conditions, but the analysis of cyclic loading of dental implants has not been done with finite element studies as it consumes a lot of time with extremely high computer resources [20].…”
Section: Discussionmentioning
confidence: 99%